Strategic management accounting and information important for production control - Nazarova, V.; Shtiller, M. (Journal of Economic Research & Business Administration, 2016)
One of the areas of industrialinnovative development of Kazakhstan is a strategic management accounting. It is associated with the production, taking into account, in which all costs are collected and calculated produc tion cost of products, which depends on the profitability of enterprises. Accounting related nature and scope of the financial information provided by the company to the users who may have different categories of people. Strategic management accounting aims to prepare information for internal users, necessary for making management decisions, ie, decisions for the future. There should be detailed information on the expected costs and revenues of the organization. At the founding of the company its owners in most cases, from a strategic, longterm installations, and not from short term considerations, which gives reason to apply accounting estimates in forecasting and analytical work. Therefore, considerable attention is now being given the strategic management accounting that has arisen relatively recently, but already formed in a fairly broad area of scientific and practi cal activities.